Implementasi Pancasila sebagai Perilaku Mahasiswa dalam Kehidupan Kampus - Naysilla Nur Ramadani; Rio Ferdinand; Arieza Habib; Marcellino Julian Pandova; Daffa Darma Atmamijaya; Seto Cahyono (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Pancasila, as the foundation of the state and the nation's philosophy of life, plays a crucial role in building the character of the younger generation, including students as agents of change. This study aims to analyze how the application of Pancasila values ​​is manifested in student behavior on campus. The method used is library research, examining various journal articles, books, and academic references related to student behavior and the practice of Pancasila values. The research findings reveal that students generally have a good understanding of Pancasila values. Values ​​such as respect, mutual assistance, equality, religiousness, and unity are recognized and accepted as guidelines for behavior on campus. However, the level of implementation is still not optimal and tends to vary between universities. Therefore, universities need to make continuous efforts to instill Pancasila values ​​through academic and non-academic activities that can strengthen students' understanding of Pancasila and strengthen its application in campus life to be more optimal and equitable.